Creativelab.printing / Luqman Haikal Zulhelmi ...[et al.] - Zulhelmi, Luqman Haikal; Abd Aziz, Muhammad Azizi; Lukman, Muhammad Izzat; Abdul Rahim, Ahmad Syakir (2023)
CREATIVELAB.PRINTING is a partnership business that provides printing and sublimation services. This partnership business has four members and five positions: general manager, administrative manager, operational manager, marketing manager, and financial manager. The primary goal of this business is to offer our customers a various selection of jersey designs. Also available in a variety of jersey styles such as collar, round neck, long sleeve, and more. We have extensive and practical experience in printing and sublimation. We provide our customers with high-quality jersey materials and custom designs based on their requirements. In addition, we promise to provide our customers with the best price in the market while maintaining high quality. Our target customers are colleagues, companies, schools, and other organizations that need to customize their jerseys for group identities. Our business forecast for the first year of our business is RM432,000.